Mr. Brickinden diary - Brickinden, Mr.
Diary of travels by a Mr. Brickinden, from Hamilton, Bermuda to the United States and Canada, including New York State and Niagara Falls. Also includes drawings and watercolor sketches of sites in Bermuda and the United States.
Collection material in English.
Keywords: Bermuda Islands -- Description and travel; Hamilton (Bermuda Islands) -- Description and travel; New York (State) -- Description and travel; Niagara Falls (N.Y. and Ont.)